TiO2 nanotube arrays based flexible perovskite solar cells with transparent carbon nanotube electrode. (January 2015) - Wang, Xiaoyan; Li, Zhen; Xu, Wenjing; Kulkarni, Sneha A.; Batabyal, Sudip K.; Zhang, Sam; Cao, Anyuan; Wong, Lydia Helena
Abstract: A solid-state, flexible solar cell based on titanium (Ti) foil/TiO2 nanotubes (TNTs) with organic–inorganic halide perovskite absorber and transparent carbon nanotube electrode is demonstrated. TNT arrays together with an inherent blocking layer were simultaneously formed on Ti foil during one-step anodization. TNT arrays serve as deposition scaffold and electron conductor for perovskite absorber. Transparent conductive carbon nanotube network is laminated on top of perovskite and serves as hole collector as well as transparent electrode for light illumination. Under AM 1.5, 100 mW cm −2 illumination, power conversion efficiency of 8.31% has been achieved, which is among the highest for TiO2 nanotube based flexible solar cells. Interestingly, up to 100 mechanical bending cycles show little deterioration to the device performance, demonstrating good flexibility of the Ti foil based perovskite solar cells. The Ti foil based solid-state, flexible perovskite solar cells have great potential for applications in building photovoltaics and wearable electronic devices. Graphical abstract: Highlights: Flexible perovskite solar cell was fabricated on Ti substrate with TiO2 NT. Transparent CNT electrode collected holes from perovskite. Effects of TiCl4 treatment and Ti foil thickness on cell performance were studied. A power conversion efficiency of 8.31% was achieved. Mechanical bending didn't deteriorate the cell performance.